PENILAIAN RISIKO KESEHATAN KERJA PADA FASILITAS PROSES DI PT X SUMATERA SE - Lestari, Ayu Seftiani (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
PT X is oil and gas production operations. Production operations are carried out in process facilities, which include oil stations and power plants. The increasing development of oil and gas companies as well as the increasing involvement of the number of workers in this sector have caused the worker very potential to be exposed to hazards in a workplace. HRA is a semi-quantitative risk assessment that determine the magnitude of risk and take control priorities. The purpose of this study was to determine the description of work activities, identify potential hazards, exposure level, and to determine the health risks that may arise, and to determine the control priority based on the Risk Manageability Matrix. This study used descriptive survey, observational approach that uses Walk Through Survey, where results are walking through the checklist, and then analyzed in Matrix Hazard Rating, Matrix Exposure Rating, Risk Matrix, and developed into Risk Manageable Matrix. The results of this study found that the potential hazards included in the moderate risk category are noise, benzene, ergonomics and psychosocial. While the low-risk category is water supply. Potential hazards with moderate risk with low level of control are noise and benzene. Due to the control and prevention efforts against the risk of exposure are not optimal, based on these results, expected of PT X can be done by applying noise control with Hearing Conservation Program, such as evaluating noise exposure. As for benzene exposure, expected that there will be biomonitoring measurements for workers and provide a warning sign to use a respirator with an organic vapor cartridge in process facility.